Примена на нанокомпозити од полианилин (PANI) со графен и повеќеслојни јаглеродни наноцевки (MWCNT) во сензори за детектирање на pH вредност на течна средина - Петровски, Александар (Технолошко-металуршки факултет, УКИМ, Скопје, 2017)
The subject of of this doctoral thesis is to develop an electrochemical process for obtaining nanocomposites of PANI with GR and MWCNT. Purpose for which these nanocomposites are made, is their application in the fabrication of nanosensors that will be used for detection of the pH changes in liquid medium. In order to determine the conditions under which electropolymerization of aniline to PANI occurs, the system consisting of 0.1 M aniline and 0.5 M H2SO4 was examined by potentiodynamic and potentiostatic methods such as cyclic voltammetry and steady state polarization. These tests showed that the conductive emeraldine form of PANI can be obtained at the potential of 0.75 V vs. SCE. As a working and counter electrodes Pt tiles with surface of 10 cm2 were used. Experiments are conducted in standard electrochemical cell with a volume of 250 ml. During the experiments several types of nanocomposites with GR and MWCNT were prepared. CNS concentration varies from 1, 2, 3 and 10% vs. the weight of the aniline in electrolyte. Besides that the type and the concentration of CNS varies, also varies the input method of CNS in the polymer matrix. First nanocomposites are made by applying the CNS on the electrode surface and then carried out the electropolymerization of PANI. The second nanocomposites are made by input the CNS in the electrolyte. Also, the impact of purification and functionalization of CNS is examined. The resulting nanocomposites were analized by SEM, Raman spectroscopy, ATR-FTIR, UV-Vis and Thermogravimetric analysis. For testing the electrical conductivity of nanocomposites, four probe method was used. In the last phase of the experiments the preparation of nanosensors was conducted and also sensor activity was tested. For this purpose the nanocomposites were inflicted on commercial gold electrodes. Due to the change of nocomposites carrier (gold), new analyses of this system were conducted using steady state polarization. Also the nanocomposites were examined by SEM and ATR-FTIR. Analysis of sensor activity was conducted in synthetic and real seawater by monitoring the changes in electrical resistance vs. the changes in pH of the water. For this purpose two probe method was used.
Докторска дисертација одбранета во 2017 година на Технолошко-металуршкиот факултет во Скопје, под менторство на проф. д–р Александар Димитров.
Keywords: Polyaniline, Graphene, Multiwalled carbon nanotubes, Electropolymerization, Nanocomposites, Nanosensors